Chronic Limb Ischemia: Awareness and Treatment in Primary Care - Purwowiyoto, Sidhi Laksono; Halomoan, Reynaldo (Sanus Medical Journal, 2023)
Chronic limb ischemia (CLI) is a type of peripheral arterial disease (PAD) that is still underdiagnosed and undertreated despite the increasing incidence, thus becoming a global health burden. The prevalence of PAD is quite high, approximately around 200 million globally in the adult population and increased drastically in older age population. It might be difficult to diagnose at an early stage because around 20-50% patients may be asymptomatic. More than 70% of primary physicians also did not notice that the diagnosis was already established during screening of the PAD patients. All these problems could increase the incidence of PAD in the following year. The untreated conditions will develop into a more severe form of PAD known as chronic limb-threatening ischemia (or critical limb ischemia), and patients are at a higher risk of having limb loss, and also increased morbidity and mortality. The primary physicians in the primary health facilities hold an important role in the early diagnosis and management of patients with CLI symptoms or with risk factors of CLI. Due to the limitation of diagnostic testing modality at primary health facilities, the physician can assess the ankle-brachial index (ABI) to determine the presence of CLI. Management of the disease is different for every patient and is customized based on the other comorbidities. Risk factors should be controlled in order to achieve a better outcome. A good management strategy will improve the condition. This review aims to describe how to give an early diagnosis and management for CLI patients in primary health care.